Está en la página 1de 1

Bài 51:

⋅ ⋅ 2
m m m  ⋅ ⋅

Τ= 1 y 2 + 22 l 2 sin 2 ϕ ϕ 2 + 22  l cos ϕ ϕ + y 
2 
 
U = − m2 gl cos ϕ
. . . .
m m m
L = T − U = 1 y 2 + 2 l 2 ϕ 2 = m2 l cos ϕ ϕ y + 2 y 2 + m2 lg cos ϕ
2 2 2
 
d  ∂L  d  2 2 . 
. .. .. . .
 .  =  m l ϕ + m2 l y cos ϕ  = m2 l 2 ϕ + m2 l y cos ϕ − m2 l y sin ϕ ϕ
dt  dt 
 ∂ ϕ  
 
. .
∂L
= − m2 l ϕ y sin ϕ − m gl sin ϕ
2
∂ϕ
 
d  ∂L  ∂L
 − =0
dt  .  ∂ϕ
 ∂ϕ 
 
.. ..

lϕ + y cos ϕ + g sin ϕ = 0
 
d  ∂L   .. 
.
d  
.. . .. ..
  = m1 y +  m2 l cos ϕ ϕ  + m2 y = y ( m1 + m2 ) + m2 l ϕ cos ϕ − ϕ 2 sin ϕ 

dt  .  dt    
∂ y
 
d  
. .
∂L
= 0; ( m1 + m2 ) y + m2 l ϕ cos ϕ  = 0
∂y dt  